Novel temperature stable NiSnTa2O8 microwave dielectric ceramics with trirutile structure. Issue 5 (1st April 2020) - Li, Enzhu; Wen, Qingyu; Yang, Hongcheng; Yang, Hongyu; Yang, Qiu; Zhang, Shuren
Abstract: A novel low-loss and temperature stable NiSnTa2 O8 ceramic with trirutile structure was prepared using traditional solid-state method. The structure-performance relationships were investigated by Rietveld refinement, chemical bond theory and far-infrared spectrum. The results show that the relative densities play a dominant role in the change of dielectric constant. Theoretical dielectric constant calculated via bond theory, Clausius-Mossotti equation and fitted result of far-infrared spectrum are close to experimental value. Ta–O bonds with greatest bond ionicity and bond energy have the primary contributions to dielectric polarizabilities and dielectric loss. The optimal microwave dielectric performances of NiSnTa2 O8 ceramics were obtained: εr ∼21.04, Q×f ∼31328 GHz and τ f = −2.63 ppm/ ° C at 1425 °C.